Venous thromboembolism: Risk profile and management of prophylaxis in gynaecological surgery patients - Janine Potgieter; Leon Snyman (South African Medical Association, 2014)
Objectives. This study aims to describe the venous thromboembolism (VTE) risk profile of women undergoing elective gynaecological surgery in a tertiary hospital and to audit the VTE prophylaxis prescribed.Methods. One hundred and nine women who underwent elective gynaecological surgery at Kalafong Provincial Tertiary Hospital were assessed in terms of their risk of developing perioperative VTE, using the modified Caprini VTE risk assessment model. An audit of the VTE prophylaxis they received was conducted postoperatively.Results. Of the 109 women, 45% were classified as at very high risk for VTE, 38% as at high risk, 14% as at moderate risk and 3% as at low risk. The audit revealed that only 5% of patients received the correct VTE prophylaxis, 55% received inadequate prophylaxis and 40% received no prophylaxis.Discussion. The majority of patients undergoing elective gynaecological surgery are either at high risk or very high risk for developing postoperative VTE-related morbidity. This group of patients require formal preoperative VTE risk assessment using a recognised scoring model. VTE prophylaxis should be administered according to recognised guidelines to avoid inadequate prophylaxis.